2015
DOI: 10.1186/s12889-015-2494-7
|View full text |Cite
|
Sign up to set email alerts
|

How well do WHO complementary feeding indicators relate to nutritional status of children aged 6–23 months in rural Northern Ghana?

Abstract: BackgroundThough the World Health Organization (WHO) recommended Infant and Young Child Feeding (IYCF) indicators have been in use, little is known about their association with child nutritional status. The objective of this study was to explore the relationship between IYCF indicators (timing of complementary feeding, minimum dietary diversity, minimum meal frequency and minimum acceptable diet) and child growth indicators.MethodsA community-based cross-sectional survey was carried out in November 2013. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
61
17
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 30 publications
23
61
17
9
Order By: Relevance
“…This relationship has been reported in the literature from developing countries including Ghana [14,26], Tanzania [27], Ethiopia [24], Cambodia [3] and India [28]. In spite of this widespread identification of the male susceptibility to stunting, the exact factors underlying it have yet to be well understood [14] but likely to be biological [29]. Short maternal stature was associated with higher odds of child stunting in present study.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…This relationship has been reported in the literature from developing countries including Ghana [14,26], Tanzania [27], Ethiopia [24], Cambodia [3] and India [28]. In spite of this widespread identification of the male susceptibility to stunting, the exact factors underlying it have yet to be well understood [14] but likely to be biological [29]. Short maternal stature was associated with higher odds of child stunting in present study.…”
Section: Discussionsupporting
confidence: 42%
“…Male children were also more likely to be stunted compared to female children. This relationship has been reported in the literature from developing countries including Ghana [14,26], Tanzania [27], Ethiopia [24], Cambodia [3] and India [28]. In spite of this widespread identification of the male susceptibility to stunting, the exact factors underlying it have yet to be well understood [14] but likely to be biological [29].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, a study from Senegal showed that HAZ was positively associated with the WHO indicators up to one year of age but less strongly as children became older, which may explain why we saw no significant results at 36 months of age between diet and linear growth [24]. Further, our results are in line with another study from Ghana which showed that these indicators better explain WHZ-scores than HAZscores for young children because the tool reflects current diet rather than habitual intake [25].…”
Section: Discussionsupporting
confidence: 86%
“…Berdasarkan hasil uji chi square diperoleh nilai p = 0,002 jika dibandingkan dengan nilai α = 0.05, maka nilai p = 0,002 kurang dari 0,05 sehingga dapat diinterpretasikan bahwa terdapat hubungan yang bermakna antara frekuensi pemberian MP-ASI dengan kejadian stunting pada anak usia 6-24 bulan Desa Leyangan Kecamatan Ungaran Timur Kabupaten Semarang. Hal tersebut sejalan dengan penelitian Saaka (2015) dengan adanya hubungan yang bermakna antara frekuensi pemberian MP-ASI dengan kejadian stunting (p = 0,06 ; p value < 0,05 Berdasarkan hasil uji korelasi chi square diperoleh nilai p value 0,015 jika dibandingkan dengan nilai α = 0.05, maka nilai p = 0,015 kurang dari 0,05 sehingga dapat diinterpretasikan terdapat hubungan yang bermakna antara tekstur MP-ASI yang diberikan dengan kejadian stunting pada anak usia 6-24 bulan di Desa Leyangan Kecamatan Ungaran Timur Kabupaten Semarang. Hasil penelitian ini sejalan dengan penelitian yang dilakukan oleh Sreedhara (2013) yaitu ada hubungan antara konsistensi atau tekstur MP ASI yang diberikan dengan kejadian stunting dan nilai p value = 0,001 (p < 0,05).…”
Section: Hubunganunclassified